Long-term anti-tumor effects following both conventional radiotherapy and FLASH in fully immunocompetent animals with glioblastoma - Emma Liljedahl; Elise Konradsson; Emma Gustafsson; Karolina Förnvik Jonsson; Jill K. Olofsson; Crister Ceberg; Henrietta Nittby Redebrandt (Scientific Reports, 2022)
Abstract Radiotherapy can induce an immunological response. One limiting factor is side effects on normal tissue. Using FLASH radiotherapy, side effects could possibly be reduced. The efficacy of FLASH in relation to conventional radiotherapy (CONV-RT) has not been extensively explored in fully immunocompetent animals. Fully immunocompetent Fischer 344 rats were inoculated with NS1 glioblastoma cells subcutaneously or intracranially. Radiotherapy was delivered with FLASH or CONV-RT at 8 Gy × 2 (subcutaneous tumors) and 12.5 Gy × 2 (intracranial tumors). Cured animals were re-challenged in order to explore long-term anti-tumor immunity. Serum analytes and gene expression were explored. The majority of animals with subcutaneous tumors were cured when treated with FLASH or CONV-RT at 8 Gy × 2. Cured animals could reject tumor re-challenge. TIMP-1 in serum was reduced in animals treated with FLASH 8 Gy × 2 compared to control animals. Animals with intracranial tumors survived longer when treated with FLASH or CONV-RT at 12.5 Gy × 2, but cure was not reached. CONV-RT and FLASH were equally effective in fully immunocompetent animals with glioblastoma. Radiotherapy was highly efficient in the subcutaneous setting, leading to cure and long-term immunity in the majority of the animals.